1980
DOI: 10.14198/mdtrra1980.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Estructura y funcionalismo de un encinar montano en el Montseny. II: biomasa arbórea

Abstract: OBJETIVOSLa finalidad del presente trabajo, parte de cu yos resultados se exponen en este artículo, es determinar la biomasa, mineralomasa y producción del encinarmontano de La Castanya (Montseny, provincia de Barcelona). En la primera fase del trabajo nos propusimos determinar la biomasa total y la de cada una de las distintas frac_ ciones (madera de 0 ^ 5 cm, madera de 0 < 5 cm, brotes de 1 y 2 años, hojas repartidas por clases de edad, cojr teza) del estrato arbóreo . Las muestras tomadas con tal finalidad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…General features of 14 Holm oak forests and woodlands of the Western Mediterranean basin were compared before selecting a zone for intensive measurements of canopy structure and understory light. This preliminary analysis revealed that canopy height decreased and basal area increased with stem density, the latter being low or medium under traditional management and high when woodlands are abandoned (results from 400-2700 sampling plots in the Spanish provinces of Madrid, Cádiz, Málaga, Huelva, Almería, Córdoba, Jaén, Sevilla and Granada -National Forestry Inventory -, and mean values reported for Gardiole de Rians, France [30], La Bruguiere, France [15], Riofrío, Segovia, Spain [45], Maremma National Park, Italy [34], La Castanya, Spain [19], and Prades, L'Avic, La Teula and B. Tornés, Spain [21,42]). The area between 40…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…General features of 14 Holm oak forests and woodlands of the Western Mediterranean basin were compared before selecting a zone for intensive measurements of canopy structure and understory light. This preliminary analysis revealed that canopy height decreased and basal area increased with stem density, the latter being low or medium under traditional management and high when woodlands are abandoned (results from 400-2700 sampling plots in the Spanish provinces of Madrid, Cádiz, Málaga, Huelva, Almería, Córdoba, Jaén, Sevilla and Granada -National Forestry Inventory -, and mean values reported for Gardiole de Rians, France [30], La Bruguiere, France [15], Riofrío, Segovia, Spain [45], Maremma National Park, Italy [34], La Castanya, Spain [19], and Prades, L'Avic, La Teula and B. Tornés, Spain [21,42]). The area between 40…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…The sample of branches less than 1 cm in diameter was separated into foliage and twigs prior to drying, in order to know the foliage weight. Fifty-six holm oaks were felled (28 from northfacing slopes and 28 from south-facing slopes) which, together with 15 trees from the study carried out by Ferris et al (1980), make up a total of 71 trees treated in this work.…”
Section: Study Areamentioning
confidence: 99%
“…Allometric equations were already available for holm oak at Montseny (Ferris et al, 1980), obtained from 15 trees felled next to an experimental plot set up for monitoring nutrient cycling studies (Terradas et al, 1980;Ferris et al, 1984). It is accepted that the allometric equations for a species in a given area can be obtained from a detailed study of 15 trees covering the whole range of diameters (Duvigneaud, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Mientras que los departamentos de las Universidades de Barcelona iniciaban en la zona de la Castanya, en el Montseny, los trabajos cuyos resultados iniciales figuran en , TERRADAS et al (1980), FERRES et al (1980), RODA et al (1980, el departamento de Biología de la Universidad de Alicante comenzaba un proceso de búsqueda de la zona más idónea para abordar el proyecto con la técnica de la cuenca impermeable de pequeña extensión.…”
Section: Introductionunclassified